Application of Multimedia Learning for Pancasila and Citizenship Education in SD Inpres Waingapu 3 - Mbana, Marlyn Rambu Day; Hariadi, Fajar; Mira, Trisari Dewi Novyanti B (Yayasan Kita Menulis, 2024)
PPKn is an essential subject in elementary schools to instill Pancasila values and national identity. However, the results of the End-of-Semester Assessment (PAS) at SD Inpres Waingapu 3 consistently show low PPKn scores. To address this issue, this study developed a multimedia learning application for PPKn. This application is designed to enhance student understanding of PPKn material, particularly related to Pancasila values. The SDLC (Software Development Life Cycle) Waterfall method was used in the application's development. The application's effectiveness was tested through pre-test and post-test, showing a significant increase in the average score of 79.5%. The application's usability was also tested using the System Usability Scale (SUS), with an average score of 85 and a category of